Food Safety Training for Food Handlers in the Canteen Elementary School, Yogyakarta - Dyah Suryani; Adi Heru Sutomo; Abu Tholib Aman; Suyitno Suyitno (Universitas Islam Bandung, 2021)
The knowledge in terms of food security affects the attitude that can influence the practice. A low level of knowledge can increase the prevalence of food-borne disease, especially among children. This study aimed to examine the effect of food security training on increasing knowledge, attitude, and practice. This study retrieved 87 food handlers (intervention=43, control=44) from 60 school canteens in Yogyakarta city, 2018. The quasi-experimental study used a non-equivalent design control group by using pretest and posttest. The given intervention was an interactive speech, presentation, and food security module. The statistical test used in this study were normality tests and independent t test. The majority of respondents for intervention and control groups were female (93% each). A significant increase in knowledge, attitude, and practice has been found after training (p value<0.05). There was no difference in knowledge, attitude, and practice among the control group (p value>0.05). This research finding the intervention effectively increases the knowledge, creates the positive, and increases food handlers and consumers' food security practices in the school. Public health providers should design health programs to conduct practical food security training. It is to be conducted continuously for food handlers in the school canteen. They need to remind them that knowledge is essential. Related stakeholders like schools should also provide adequate sanitation facilities and increasing supervision at the school canteen. PELATIHAN KEAMANAN PANGAN UNTUK PENJAMAH MAKANAN DI KANTIN SEKOLAH DASAR, YOGYAKARTAPengetahuan dalam hal ketahanan pangan memengaruhi sikap yang dapat memengaruhi praktik. Tingkat pengetahuan yang rendah dapat meningkatkan prevalensi penyakit bawaan makanan, terutama pada anak. Penelitian ini bertujuan menguji pengaruh pelatihan ketahanan pangan terhadap peningkatan pengetahuan, sikap, dan praktik. Penelitian ini mengambil 87 penjamah makanan (intervensi=43, kontrol=44) dari 60 kantin sekolah di Kota Yogyakarta tahun 2018. Penelitian kuasi eksperimental menggunakan desain kelompok kontrol non-ekuivalen dengan menggunakan pretest dan posttest. Intervensi yang diberikan adalah pidato interaktif, presentasi, dan modul ketahanan pangan. Uji statistik yang digunakan dalam penelitian ini adalah uji normalitas dan uji t independen. Responden kelompok intervensi dan kontrol mayoritas berjenis kelamin perempuan (masing-masing 93%). Peningkatan signifikan pada pengetahuan, sikap, dan praktik ditemukan setelah pelatihan (p<0,05). Tidak ada perbedaan pengetahuan, sikap, dan praktik antara kelompok kontrol (p>0,05). Penelitian ini menemukan bahwa intervensi efektif untuk meningkatkan pengetahuan, menciptakan sisi positif, dan meningkatkan praktik ketahanan pangan antara penjamah makanan dan konsumen di sekolah. Petugas kesehatan masyarakat harus merancang program kesehatan untuk melakukan pelatihan ketahanan pangan yang efektif untuk dilakukan secara terus menerus bagi penjamah makanan di kantin sekolah, mengingatkan mereka tentang pengetahuan yang diberikan untuk setiap sesi dan pemangku kepentingan terkait seperti sekolah juga harus menyediakan fasilitas sanitasi yang memadai dan meningkatkan pengawasan di kantin sekolah.